2020
DOI: 10.1002/jbt.22447
|View full text |Cite|
|
Sign up to set email alerts
|

Irbesartan mitigates acute liver injury, oxidative stress, and apoptosis induced by acetaminophen in mice

Abstract: Hepatotoxicity induced by acetaminophen (APAP)-overdose is a major concern in clinical practice. In the present work, the detoxifying effect of irbesartan (Irb) on the APAP-induced acute liver injury was evaluated in mice. Induction of acute liver injury in mice was established by a single intraperitoneal (IP) injection of APAP (0.5 g/kg), then mice were injected with Irb (50 or 75 mg/kg, IP), each given twice at 1 and 12 hours post APAP injection. Liver functions, hepatic oxidative and nitrosative stress mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 52 publications
(75 reference statements)
1
14
0
Order By: Relevance
“…In the current study, IRB administration afforded protection to the uterus against EB-induced oxidative stress. Consistent with this result, several previous studies demonstrated similar findings relating to the ability of IRB to decrease oxidative stress through a significant reduction in MDA level with a significant increase in SOD activity [24,25], may be partly through AT1R blockade, as Ang II can result in oxidative stress [32], and PPARγ agonistic activity [33].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the current study, IRB administration afforded protection to the uterus against EB-induced oxidative stress. Consistent with this result, several previous studies demonstrated similar findings relating to the ability of IRB to decrease oxidative stress through a significant reduction in MDA level with a significant increase in SOD activity [24,25], may be partly through AT1R blockade, as Ang II can result in oxidative stress [32], and PPARγ agonistic activity [33].…”
Section: Discussionsupporting
confidence: 81%
“…This directed our attention to examine the possible unexplored protective mechanisms of IRB, an AT1R blocker with PPARγ agonistic activity [ 23 ], in EH. For example, IRB shows anti-inflammatory and antioxidant properties [ 24 , 25 , 26 ], two actions that are expected to be efficacious in the prevention of EH. The results showed that EB succeeded in the induction of EH as evidenced by the significant increase in uterine weights, MDA, TNFα, survivin with a concomitant decrease in SOD, cleaved caspase 3, IL10, and PPARγ, besides typical histopathological features of EH and atypia.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen (APAP) is widely utilized as an over-the-counter drug for treating inflammation, fever, as well as pain [ 1 ]. APAP is currently the main antipyretic and analgesic drug recommended by several studies over non-steroidal anti-inflammatory drugs (NSAIDs) used to manage fever and pain associated with the pandemic infection of coronavirus 2019 (COVID-19).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption could cause a possible misuse of acetaminophen, which is considered the major cause behind drug-induced liver injury (DILI) worldwide. [ 1 3 ]. Although N -acetylcysteine (NAC) is the current drug used to protect against liver injury induced by APAP, it is only effective when given an early period of APAP ingestion and associated with adverse effects such as nausea, vomiting, allergic reactions, and headaches [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Wu et al [27] revealed that increased caspase-3 expression in APAP treated mice was observed around CV. In addition, Irbesartan mitigated APAP-induced caspase-3 expression in mice model [28]. Similarly, Li et al [29] showed that apoptosis, induced by activated HSCs, is characterized by increased caspase-3 in-vitro.…”
Section: Abdel-bakky Ms Et Almentioning
confidence: 86%